The nexus of knowledge sharing on job satisfaction: dual mediation of individual adaptability and learning commitment - Bimmo Dwi Baskoro; Iriana Wihardja; Bernard Tirto Widjaja (Universitas Negeri Padang, 2022)
This research aimed to test and analyse the effects of knowledge sharing practices towards job satisfaction mediated by individual adaptability and learning commitment. The subjects of this research were all employees at a Telecommunication Company, domicilied in Batam and the total employees were 116. This was a causal associations research and used quantitative approarch. The data collection of this research was saturation sampling. The data was collected with tested questionnaire and it used SEM-PLS. The result showed that knowledge sharing practices, individual adaptability, and learning commitment affected to job satisfcation. Learning commitment and individual adaptability mediated the effects of knowledge sharing practice towards job satisfaction. This is the first study to discuss the effects of organization knowledge sharing practices towards employees’ individual adaptability, learning commitment, and job satisfaction, in the context of telecommunication sector in Batam.